2013
DOI: 10.1111/mmi.12363
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an archaeal ketopantoate reductase and its involvement in regulation of coenzyme A biosynthesis

Abstract: SummaryCoenzyme A (CoA) biosynthesis in bacteria and eukaryotes is regulated primarily by feedback inhibition towards pantothenate kinase (PanK). As most archaea utilize a modified route for CoA biosynthesis and do not harbour PanK, the mechanisms governing regulation of CoA biosynthesis are unknown. Here we performed genetic and biochemical studies on the ketopantoate reductase (KPR) from the hyperthermophilic archaeon Thermococcus kodakarensis. KPR catalyses the second step in CoA biosynthesis, the reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 60 publications
3
30
0
Order By: Relevance
“…As there is only one KPR that has been characterized from a hyperthermophile (17), it is difficult to judge, from a biochemical viewpoint, whether the catalytic efficiency of Tm-KPR/KARI is sufficient to conclude that it can act as (27). As T. maritima lacks the classical KPR gene, the relatively higher ratio of KPR activity against KARI activity in Tm-KPR/KARI than that in the E. coli KARI may reflect the fact that the protein does function as a KPR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As there is only one KPR that has been characterized from a hyperthermophile (17), it is difficult to judge, from a biochemical viewpoint, whether the catalytic efficiency of Tm-KPR/KARI is sufficient to conclude that it can act as (27). As T. maritima lacks the classical KPR gene, the relatively higher ratio of KPR activity against KARI activity in Tm-KPR/KARI than that in the E. coli KARI may reflect the fact that the protein does function as a KPR.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found that TM0550 was 54.5% identical to the ketol-acid reductoisomerase (KARI) of C. glutamicum, which displays KPR activity (7). As type III PanKs are considered to be unaffected by CoA, we first focused on the KPR reaction, as this is the target of feedback inhibition in archaeal CoA biosynthesis (17). We thus examined whether the KARI homolog TM0550 corresponded to KPR in T. maritima and whether it was inhibited by CoA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NAD ϩ is also the starting material for ADP-ribosylation of proteins, a type of posttranslational modification found in eukaryotes and a number of bacteria (2,3). The presence of NAD ϩ -dependent enzymes has been demonstrated in a number of hyperthermophiles (4)(5)(6)(7)(8). However, it is also known that NAD ϩ is readily degraded at high temperature as well as at high pH (9,10).…”
mentioning
confidence: 99%